2013
DOI: 10.1136/bmjopen-2012-002395
|View full text |Cite
|
Sign up to set email alerts
|

Amputations and socioeconomic position among persons with diabetes mellitus, a population-based register study

Abstract: ObjectiveLow socioeconomic position is a known health risk. Our study aims to evaluate the association between socioeconomic position (SEP) and lower limb amputations among persons with diabetes mellitus.DesignPopulation-based register study.SettingFinland, nationwide individual-level data.ParticipantsAll persons in Finland with any record of diabetes in the national health and population registers from 1991 to 2007 (FinDM II database).MethodsThree outcome indicators were measured: the incidence of first major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 30 publications
(23 reference statements)
6
41
1
1
Order By: Relevance
“…(30) They are also similar to findings from a recent observational study in Finland that demonstrated a significant association between diabetic lower extremity amputation rate and socioeconomic status, with an approximately two-fold increase from lowest to highest socioeconomic status strata, despite universal access to health services. (10)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(30) They are also similar to findings from a recent observational study in Finland that demonstrated a significant association between diabetic lower extremity amputation rate and socioeconomic status, with an approximately two-fold increase from lowest to highest socioeconomic status strata, despite universal access to health services. (10)…”
Section: Discussionmentioning
confidence: 99%
“…(7, 8) Evidence shows that patients residing in low-income households receive lower quality diabetes care, even in settings where universal coverage for primary health care exists. (9, 10) Several studies have used mapping methods to assess diabetes-related processes and outcomes, including neurologic and renal complications (11), diabetes prevalence and treatment resources (12), and effectiveness of targeted programs to improve quality of diabetes care in zip codes with high minority populations (13). Other existing studies have analyzed disparities in diabetic amputations, but have generally focused on specific patient sub-groups or settings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Számos tanulmány bizonyította, hogy ha az alapvető demográfiai, epidemiológiai jellemzőkön túl bővítjük a számba veendő potenciálisan meghatározó tényezők kö-rét, számos, társadalmi szerepre, gazdasági állapotra vonatkozó tényező ismerhető fel, amelyek egyértelmű ösz-szefüggést mutatnak az amputációs adatokkal. Finn, amerikai, ausztrál és angol közlemények számolnak be arról, hogy a lakóhely, a településméret, a népsűrűség, az iskolai végzettség, a jövedelem, a foglalkoztatottság, az egészségügyi ellátáshoz való hozzájutás, a biztosítási ál-lapot, a rassz, az etnikum, a higiéniás viszonyok mind olyan tényezők, amelyek szerepe az amputációk előfor-dulásában nem elhanyagolható [33][34][35][36]. Ezekből a té-nyezőkből képzett deprivációs indexek szintén magyarázhatják az észlelt egészség egyenlőtlenséget.…”
Section: Táblázatunclassified
“…Numerous variables are involved in its etiology and complications. The long duration of the disease and poor metabolic control [3,4] demonstrated by the high glycated hemoglobin and fasting glycemic levels in the amputee groups, reinforce the higher risk of amputation in these patients, as well of the higher frequency of fatal cardiovascular events.…”
Section: Critical Lower Limb Ischemiamentioning
confidence: 99%